2015
DOI: 10.2147/ijwh.s78874
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitudes of Latin American gynecologists regarding unplanned pregnancy and use of combined oral contraceptives

Abstract: BackgroundUnintended pregnancy is a public health problem and unmet medical need worldwide. It is estimated that in the year 2012, almost 213 million pregnancies occurred, and the global pregnancy rate decreased only slightly from 2008 to 2012. It was also estimated that 85 million pregnancies (40% of all pregnancies) were unintended and that 38% ended in an unintended birth.ObjectivesTo assess knowledge and attitudes of Latin American (LA) obstetricians and gynecologists (OBGYNs) regarding unintended pregnanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In our study, only 5% of participants received information about birth control methods from a doctor, who usually informed the adolescent only about condoms. The rationale for this approach is that all other methods of contraception supposedly cause damage to the adolescent, which was demonstrated by Bahamondes et al [48], who identified some deficiencies and contradictions in knowledge and attitudes based on responses from Latin American obstetricians and gynecologists who participated in the survey. In Mexico, de Castro et al [24], conducted a study where some adolescents pretended to be clients visiting pharmacies and healthcare facilities, asking for contraceptives.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, only 5% of participants received information about birth control methods from a doctor, who usually informed the adolescent only about condoms. The rationale for this approach is that all other methods of contraception supposedly cause damage to the adolescent, which was demonstrated by Bahamondes et al [48], who identified some deficiencies and contradictions in knowledge and attitudes based on responses from Latin American obstetricians and gynecologists who participated in the survey. In Mexico, de Castro et al [24], conducted a study where some adolescents pretended to be clients visiting pharmacies and healthcare facilities, asking for contraceptives.…”
Section: Discussionmentioning
confidence: 99%
“…[89] Health care providers not only need to be able to proactively address common myths and misconceptions around the suitability and potential side effects of different contraceptive methods but also correct inaccurate perception of the frequency with which side effects occur. [86][87][88]90] Accurate information regarding the relationship with hormonal contraception and certain cancers, including the well documented decrease in the risk of ovarian and endometrial cancers, should be provided. [90] In all countries, HCPs may need guidance in identifying situations where it is appropriate to explore the non-contraceptive benefits of hormonal methods, such as management of heavy menstrual bleeding, painful periods, polycystic ovary syndrome (PCOS), or acne.…”
Section: Health Care Professional Educationmentioning
confidence: 99%
“…[86][87][88]90] Accurate information regarding the relationship with hormonal contraception and certain cancers, including the well documented decrease in the risk of ovarian and endometrial cancers, should be provided. [90] In all countries, HCPs may need guidance in identifying situations where it is appropriate to explore the non-contraceptive benefits of hormonal methods, such as management of heavy menstrual bleeding, painful periods, polycystic ovary syndrome (PCOS), or acne. [78,90] Effective counselling techniques Concepts such as the GATHER approach (see Figure 4) [91] may be helpful in structuring the counselling of adolescent women.…”
Section: Health Care Professional Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the third publication of the data obtained through a multiple-choice questionnaire completed by LA OBGYNs using an Interactive Audience Systems Response on occasion of a scientific meeting in Chile organized by Bayer HealthCare in the last quarter of 2014 [ 11 , 12 ]. The OBGYNs came from 12 countries (Argentina, Bolivia, Brazil, Chile, Colombia, Costa Rica, Ecuador, Guatemala, Mexico, Paraguay, Peru, and Venezuela).…”
Section: Methodsmentioning
confidence: 99%